International trade, technological shocks and spillovers in the labour market: A GVAR analysis of the US manufacturing sector - Paul Hiebert; Isabel Vansteenkiste (European Central Bank (ECB), 2007)
We empirically analyse the response of US manufacturing labour market variables to various shocks, notably to trade openness and technology. The econometric approach involves an application of the recently developed global VAR (GVAR) methodology of Dees, DiMauro, Pesaran, and Smith (2005) to 12 manufacturing industries over the period 1977-2003. This frame-work allows for an assessment of both shocks to weakly exogenous variables and intra-industry spillovers. In this vein, beyond a standard set of labour-market related variables (employment, real compensation, productivity and capital stock) and exogenous factors (a sector-specific measure of trade openness, along with common technology and oil price shocks), specific measures of manufacturing-wide variables are included for each sector. Generalised impulse responses indicate that increased trade openness negatively affects real compensation, has negligible employment effects and leads to higher labour productivity. These impacts, however, are relatively weaker those induced by technology shocks, with the latter positively and significantly affecting both real compensation and employment. There is also evidence of positive spill-overs across industries from sector-specific employment and productivity shocks. Impact elasticities suggest strong intra-sectoral linkages for employment and capital stock formation, contrasting with weak linkages for what concerns real compensation and productivity.
Keywords: F16; J01; O33; 330; Global VAR (GVAR); impulse responses; labour market; Technological Change; Trade; Arbeitsmarkt; Industrie; Internationale Wirtschaft; Technischer Fortschritt; Spillover-Effekt; VAR-Modell; USA